Structural features of the invariant chain fragment CLIP controlling rapid release from HLA-DR molecules and inhibition of peptide binding. - Kropshofer, H (1995)
The invariant chain (Ii) prevents binding of ligands to major histocompatibility complex (MHC) class II molecules in the endoplasmic reticulum and during intracellular transport. Stepwise removal of the Ii in a trans-Golgi compartment renders MHC class II molecules accessible for peptide loading, with CLIP (class II-associated Ii peptides) as the final fragment to be released. Here we show that CLIP can be subdivided into distinct functional regions. The C-terminal segment (residues 92-105) of the CLIP-(81-105) fragment mediates inhibition of self- and antigenic peptide binding to HLA-DR2 molecules. In contrast, the N-terminal segment CLIP-(81-98) binds to the Staphylococcus aureus enterotoxin B contact site outside the peptide-binding groove on the alpha 1 domain and does not interfere with peptide binding. Its functional significance appears to lie in the contribution to CLIP removal: the dissociation of CLIP-(81-105) is characterized by a fast off-rate, which is accelerated at endosomal pH, whereas in the absence of the N-terminal CLIP-(81-91), the off-rate of C-terminal CLIP-(92-105) is slow and remains unaltered at low pH. Mechanistically, the N-terminal segment of CLIP seems to prevent tight interactions of CLIP side chains with specificity pockets in the peptide-binding groove that normally occurs during maturation of long-lived class II-peptide complexes.